Mechanical properties of carbon fiber reinforced laminates and pipes - Jin, Yicheng (2015)
In this study, the improvement of mechanical properties of carbon fibre reinforced plastics (CFRP) due to application of surface treatments was investigated. Two kinds of surface treatments were carried out; one enhancing fibre and matrix interface while the other improved the interfacial strength between CFRP and titanium surface. Ultimately the study hopes to apply these enhancements to offshore structures to enhance its properties. The fibre matrix interface was modified by silanization and addition of nanofillers to the fibre surface. Woven Carbon fibre was first pretreated with Carbon Nanotubes (CNTs) dispersed in ethanol solution containing hydrolyzed silane, followed by matrix infusion through vacuum assisted resin transfer method (VARTM). Specimens were subjected to long term effect of sea water and tensile tests showed a marginal improvement in tensile strength and modulus in specimens which were subjected to treatment with silane and CNTs. Titanium pipes overwrapped with CFRP was then investigated to study effect of surface treatment of titanium on the overall pipe properties. The surface of titanium was first sand blasted and subsequently anodized with sodium hydroxide before CFRP was overlaid on the titanium. Titanium pipes overwrapped with CFRP exhibited stronger lateral compressive yield strength when the pipes were first anodized. This was attributed to stronger interfacial strength between the titanium and CFRP, which delayed the onset of delamination at the interface. Axial compression of the pipe also showed a higher compressive yield strength after surface treatment through anodization. Based on this experimental study, surface treatment has improved the overall pipe property by enhancing interfacial strength.